The influence of image and consumer factors on store brand choice in the Brazilian market. Issue 5 (10th August 2015) - Juan Carlos Sosa Varela, Dr; Diallo, Mbaye Fall; Burt, Steve; Sparks, Leigh
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the role of image and consumer factors in influencing store brand (SB) choice between two retail chains (Carrefour and Extra) in a Latin American market, Brazil. SBs are increasingly offered by retailers in emerging markets. What is less clear, however, is how emerging market consumers make their choices between the SBs on offer from different retail chains. Design/methodology/approach – A mall-intercept survey conducted by a Brazilian market research company generated 600 usable questionnaires collected in two retail chains. Structural equation modelling was used to test a series of proposed hypotheses. Findings – The results revealed that SB attitude, SB price-image, store image perceptions, SB perceived value and SB purchase intention have significant and positive direct or indirect effects on SB choice overall, and for each retail chain. However, for price-related constructs, the relationships are stronger for the Extra chain compared to the Carrefour chain. Results show that the Brazilian market presents some departures from both developed and other emerging countries. Research limitations/implications – Respondents were consumers in only one Latin American market (Brazil) and shoppers of only two retail chains. Caution should therefore be exercised when generalising the results to other markets in Latin America. Practical implications – Understanding which factors influence consumer choice of SBs in an emerging market while taking into account the presence of different operators allows retailers to launch new SB programs and implement the appropriate strategies to increase SB sales in this market. Originality/value – The main contribution of this research lies in clarifying consumer behaviour towards SBs in an emerging Latin American market. It fills a major gap in the marketing literature and research in stressing the need to rethink the application of conventional business models to Latin America.